Analysis of the Possibility of Using Energy Harvesters to Power Wearable Electronics in Clothing - Anna Dąbrowska; Agnieszka Greszta (Advances in Materials Science and Engineering)
The purpose of this study is to analyze the state-of-art knowledge of the use of energy harvesters (EHs) to power the wearables of clothing. The study discusses some examples of clothing with incorporated different types of EHs, harvesting energy from body movement (based on piezoelectric, electromagnetic, and electrostatic phenomena) from temperature differences, as well as from solar radiation. In the performed analysis, particular attention was focused on the design of EHs, their principle of operation, advantages, disadvantages, and restrictions on use. Low energy requirements of wearable electronics (e.g., sensors and diodes) implemented to clothing indicate the possibility of using miniaturized EHs as a power source for such elements. Each of the discussed EH has both disadvantages and advantages. Therefore, the selection of EH should be preceded by a detailed analysis of the conditions of the garment use, its destination, the user’s physical activity, and the energy needs of the electronic devices incorporated in clothing. Despite a variety of research studies aimed at developing new EH, relatively few of them concern their implementation in the structure of clothing and tests of their functionality in the foreseeable conditions of use. In view of the above, these issues have been addressed in this publication based on the available literature.